1994
DOI: 10.1007/bf00224806
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polybrominated biphenyls and perchlorinated terphenyls on in vitro fertilization in the mouse

Abstract: Polybrominated biphenyls (PBBs) and perchlorinated terphenyls (PCTs) are industrial chemicals that are long-lasting environmental contaminants. Although in vivo effects of PBBs on reproduction are documented, no information is available on the effects of these chemicals on sperm-egg interactions or fertilization. The present study was undertaken to determine the toxic potential of PBBs and PCTs on in vitro fertilization (IVF) in the mouse. 2-Bromobiphenyl, 4-bromobiphenyl, o-terphenyl, m-terphenyl, and p-terph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…Animal studies have demonstrated that PCBs cause reduced oocyte maturation (reviewed by Pocar et al 2006), increased embryo degeneration and decreased embryo cell proliferation, blastocyst formation and blastocyst development, and decreased IVF success rates (Campagna et al 2001, 2002; Kholkute and Dukelow 1997; Kholkute et al 1994a, 1994b; Krogenaes et al 1998; Kuchenhoff et al 1999; Lindenau and Fischer 1996; Pocar et al 2001), along with increased implantation failures (Linder et al 1974), increased resorptions (Arnold et al 1995), and decreased litter production (Jonsson et al 1975; Seiler et al 1994). PCB impacts on uterine receptivity may also contribute to an increased risk of implantation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that PCBs cause reduced oocyte maturation (reviewed by Pocar et al 2006), increased embryo degeneration and decreased embryo cell proliferation, blastocyst formation and blastocyst development, and decreased IVF success rates (Campagna et al 2001, 2002; Kholkute and Dukelow 1997; Kholkute et al 1994a, 1994b; Krogenaes et al 1998; Kuchenhoff et al 1999; Lindenau and Fischer 1996; Pocar et al 2001), along with increased implantation failures (Linder et al 1974), increased resorptions (Arnold et al 1995), and decreased litter production (Jonsson et al 1975; Seiler et al 1994). PCB impacts on uterine receptivity may also contribute to an increased risk of implantation failure.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary observations indicated that human embryos, derived from oocytes contained in follicles with elevated pollutant concentrations had low cleavage rate as observed after IVF [49]. Kholkute et al [50,51] tested the effects of EDs mixtures, such as Aroclor 1254 and 1268, on the in vitro maturation and fertilization of mouse oocytes. Their results Aromatase 5-alpha-reductase type 1 5-alpha-reductase type 2 Fig.…”
Section: Female Reproductionmentioning
confidence: 97%
“…In an in vitro study, Kholkute and Dukelow (1997) found that a mixture of PCBs resulted in adverse effects on fertilization, oocytes, and 2-cell embryos in the mouse without additive or synergistic effects. FargasovĂĄ ( 1997) that toxicity of metals (V, Mo, Mn, Ni, and Cu metal ions) in combination was different from that of individual metals to Chironomus plumosus larvae.…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 97%